PENGARUH MOTIVASI DALAM MENINGKATKAN PRESTASI KERJA KARYAWANPADA PERUSAHAAN NUSANTARA TROPICAL FARM (NTF) DI LAMPUNG TIMUR (Studi pada Karyawan Bagian Produksi) - Agustian, Didiek Wijaya (Jurnal Manajemen Magister Darmajaya, 2018)
In Nusantara Tropical Farm Company (NTF), there are problems that are lack of motivation given such as giving compensation, incentives or bonuses and attention etc. to the employees. This causes a decrease in employee morale in completing the work that is charged to employees. As for the problem in this research is